Necrotizing Bacterial Myositis as the Initial Presentation of Severe Aplastic Anaemia - Rørvik, Synne Dragesund; Larsen, Kristoffer Stange; Helgeland, Lars; Dale, Håvard; Ivarsen, Birgitta; Bruserud, Øystein; Tvedt, Tor Henrik Anderson (Case Reports in Hematology, 2021)
Introduction. Necrotizing soft tissue infections are rapidly progressing infections associated with severe inflammation and cytokine release. Early recognition and surgical intervention are key factors to secure survival. The current case presents a patient with multifocal necrotizing soft tissue infection as the initial presentation of severe aplastic anaemia. Case Presentation. A man in his fifties was admitted with septic shock with multiorgan failure and severe pancytopenia, after two days of malaise with high fever and right flank pain. The diagnosis streptococcal necrotizing myositis was significantly delayed due to atypical clinical findings. After initial surgical exploration, the decision was made to defer from surgical debridement due to extensive involvement of several muscle groups, grave pancytopenia, and suspected dismal prognosis. Surprisingly, the patient stabilized after antibiotics and intensive care treatment. Based on severe pancytopenia and hypocellular bone marrow, with no evidence of other bone marrow disorders, the patient was diagnosed with aplastic anaemia. Treatment for aplastic anaemia with antithymocyte globulin, cyclosporine, and eltrombopaq was started, and 2 months later, a partial haematological recovery was observed. The patient could be discharged from hospital without antibiotic treatment. Conclusions. This case illustrates the crucial role of a multidisciplinary approach on admission and further during the clinical course. Clinical improvement despite severe neutropenia and stabilization during immunosuppressive therapy suggest that immunological factors modulate clinical course in necrotizing soft tissue infections.